Habitual Preference for the Nondrug Reward in a Drug Choice Setting - Vandaele, Youna; Guillem, Karine; Ahmed, Serge H. (Frontiers in Behavioral Neuroscience, 2020)
For adaptive and efficient decision making, it must be possible to select between habitual alternative courses of actions. However, research in rodents suggests that, even in the context of simple decision-making, choice behavior remains goal-directed. In contrast, we recently found that during discrete trial choice between cocaine and water, water-restricted rats preferred water and this preference was habitual and inflexible (i.e., resistant to water devaluation by satiation). Here we sought to test the reproducibility and generality of this surprizing finding by assessing habitual control of preference for saccharin over cocaine in non-restricted rats. Specifically, after acquisition of preference for saccharin, saccharin was devalued and concurrent responding for both options was measured under extinction. As expected, rats responded more for saccharin than for cocaine during extinction, but this difference was unaffected by saccharin devaluation. Together with our previous research, this result clearly indicates that preference for nondrug alternatives over cocaine is under habitual control, even under conditions that normally support goal-directed control of choice between nondrug options. The possible reasons for this difference are discussed.